Substantiation of the Line for the Primary Processing of Industrial Hemp lnto Hemp of the Same Type Undirected - E. V. Novikov; I. N. Altukhova; A. V. Bezbabchenko (Сельскохозяйственные машины и технологии, 2022)
It was shown that there is a need for the research and development of domestic lines for processing two-season raw industrial hemp of autumn and spring harvesting. The lines need to be efficient, low-cost and produce fiber of various qualities.Research purpose The research aimed to substantiate the design of a low-cost line for the primary processing of technical hemp harvested in autumn and spring as a tangled mass of broken stems, and work out the recommendations for processing raw materials.Materials and methods Autumn harvest hemp was processed in four ways: single, double, triple and quadruple pass through the flax line of primary processing, without changing the settings of the machines. The design of this line was detailed as follows: DLV-2 flax disintegrator, horizontal lamellar fiber unloader of the VUL system named after I.N. Levitsky and two shaking machines with a lower combed field at the rotation frequency of a disintegrator rotor of 1000 revolutions per minute, and a swing frequency of the shaking machine needle rollers of 230 revolutions per minute. The obtained hemp was examined for quality indicators according to the current standards.Results and discussion It was revealed that the medium length of broken stems is 150 millimeters, the minimum and maximum length varies from 24 to 485 millimeters. It was shown that autumn harvest hemp is difficult to process: single and double passes of autumn harvest hemp through the line under research do not provide the desired fiber quality, which does not correspond to even the lowest grade. The third pass revealed to be possible to provide a quality fiber, and the fourth proved to be impractical.Conclusions It was proved that the separation and breaking load of the fiber in autumn harvest hemp weed differ from spring harvest hemp: 4.6 units versus 8.2-8.6 and 9.3 kilogram-force versus 13.5-16.9, respectively. The authors determined the quality indicators of hemp of the same type, undirected, and its yield with various processing options. For the first time, a domestic line for processing autumn and spring hemp with a capacity of 600 kilograms per hour and more was proposed, which allows to change the fiber quality, get a 1.5-2.0 times increase in productivity and change the fiber cost. The recommendations were substantiated for the effective hemp processing and the necessity of creating a disintegrator for hemp.